The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/mus.24324
|View full text |Cite
|
Sign up to set email alerts
|

Changes in α7β1 integrin signaling after eccentric exercise in heat‐shocked rat soleus

Abstract: Long-duration EE may cause alterations in the FA in rat soleus muscle through the α7 integrin subunit and FAK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…In skeletal muscle, RhoA protein expression decreases following 3 days of hindlimb unloading and increases following reloading (McClung et al 2004). We have seen RhoA decrease similarly to FAK following downhill running (Graham et al 2015). SRF can colocalize with both RhoA and FAK (Sakuma et al 2003) and unloading decreased SRF protein expression along with FAK protein expression in rat hindlimb muscles (Gordon et al 2001).…”
Section: Fak and Actin Dynamicsmentioning
confidence: 74%
See 2 more Smart Citations
“…In skeletal muscle, RhoA protein expression decreases following 3 days of hindlimb unloading and increases following reloading (McClung et al 2004). We have seen RhoA decrease similarly to FAK following downhill running (Graham et al 2015). SRF can colocalize with both RhoA and FAK (Sakuma et al 2003) and unloading decreased SRF protein expression along with FAK protein expression in rat hindlimb muscles (Gordon et al 2001).…”
Section: Fak and Actin Dynamicsmentioning
confidence: 74%
“…Cyclic strain decreases phosphorylation of cSrc at tyrosine 527, the main inhibitory site on this kinase, thus activating cSrc; this effect is maintained for 60 min in cultured C2C12 (Kumar et al 2004). We have observed that in rat soleus, total and activated cSrc protein expression are not affected by 90 min of eccentric downhill running at 2 and 48 h post-exercise despite decreases in FAK levels (Graham et al 2015) We have also found that cSrc activation is decreased 56 days following spinal cord injury (SCI) in rat gastrocnemius with no changes in total or activated ERK1/2 (Graham, manuscript in review). This suggests that in skeletal muscle, direct FAK and cSrc signaling through ERK1/2 may occur (1) less than 2 h following exercise; (2) during the immediate time-frame following unloading or paralysis or; (3) independently of ERK1/2 in load-induced cell signaling.…”
Section: Mechanisms For Muscle Hypertrophymentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that total and phosphorylated cSrc Y416 were not altered 2 or 48 h post-eccentric treadmill exercise. 30 In cardiac myocytes, the FAK/cSrc relationship has been implicated as being an upstream mediator of ERK1/2 activity and hypertrophy following cardiomyocyte overload. 31 This relationship must be subject to additional regulatory controls, such as changes in levels of phosphatases, because 56 days following SCI reductions in FAK and cSrc phosphorylation were not associated with altered phosphorylation of ERK1/2, even though it is necessary for growth, maintenance and regulation of muscle myotubes 32 and can be directly related to sarcolemmal tension.…”
Section: Discussionmentioning
confidence: 99%
“…Akt then activates mTORC1 ( Watson and Baar, 2014 ) ( Figure 1 ). In addition to cardiac muscle in skeletal muscle, FAK phosphorylation and β1 integrin for aerobic and anaerobic exercise (75–98% VO 2max three times a week for 8 weeks) increase immediately after exercise ( Wilkinson et al, 2008 ; Flueck et al, 2011 ; Li et al, 2013 ; Graham et al, 2015a ; Graham et al, 2015b ; Franchi et al, 2018 ) ( Table 2 ). In exercise, cardiac hypertrophy occurs with a proportional increase in collagen and possibly integrin, leading to a highly functional matrix ( Burgess et al, 2001 ).…”
Section: Extracellular Apoptosis Signaling Pathwaysmentioning
confidence: 99%